2018
DOI: 10.1007/s10461-018-2217-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Which Place Characteristics are Associated with the Odds of Recent HIV Testing in a Large Sample of People Who Inject Drugs in 19 US Metropolitan Areas

Abstract: This exploratory analysis investigates relationships of place characteristics to HIV testing among people who inject drugs (PWID). We used CDC's 2012 National HIV Behavioral Surveillance (NHBS) data among PWID from 19 US metropolitan statistical areas (MSAs); we restricted the analytic sample to PWID self-reporting being HIV negative (N = 7477). Administrative data were analyzed to describe the 1. Sociodemographic Composition; 2. Economic disadvantage; 3. Healthcare Service/Law enforcement; and 4. HIV burden o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
3
5
0
Order By: Relevance
“…Previous research measured specialized resources useful for the community action being studied. Such actions have included SPP presence and HIV testing and treatment among PWID [4][5][6][7][38][39][40], as well as a broad range of programs such as providing condom distribution interventions or programs [20,21,36], or specialized programs for treatment of people who are mentally ill [40,41]. In the present study we found that, consistent with our hypotheses, having a larger community, public health, and social work workforce in MSAs predicted higher treatment coverage levels.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Previous research measured specialized resources useful for the community action being studied. Such actions have included SPP presence and HIV testing and treatment among PWID [4][5][6][7][38][39][40], as well as a broad range of programs such as providing condom distribution interventions or programs [20,21,36], or specialized programs for treatment of people who are mentally ill [40,41]. In the present study we found that, consistent with our hypotheses, having a larger community, public health, and social work workforce in MSAs predicted higher treatment coverage levels.…”
Section: Discussionsupporting
confidence: 85%
“…Despite this, however, relatively little is known about what determines their presence and reach. Much health policy discourse assumes that need for a program is associated with program presence or magnitudehowever our previous studies of the determinants of drug treatment coverage and syringe exchange presence have found that need is not a predictor of these programs for PWID [4][5][6][7]38]. The present study, similarly, has found that several key indicators of need were not related to 1993-2007 drug treatment coverage.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…Bellatorre et al () are among the first to empirically link segregation to allostatic load and Hao et al () extended segregation to cancer survivors' health‐related quality of life, though Massey () already proposed a theoretical connection between segregation and allostatic load. It should be noted that since 2017, several scholars have reported that segregation is related to the availability of health care resources (Caldwell et al, ), health behaviors (Tempalski et al, ; Thomas‐Hawkins et al, ), and neurological disorder (Pennap et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Four of the seven studies that explicitly measured white/Asians segregation found that Asians benefited from high segregation in terms of low risk of having a low birth weight baby and smoking during pregnancy (Walton, ; Yang et al, ), low odds of late‐stage breast cancer diagnosis (Mobley, Kuo, et al, ) and early‐stage breast cancer surgery (Ojinnaka et al, ), and low sodium‐potassium ratio (Yi et al, ). Thirteen studies did not find a significant relationship between racial/ethnic segregation and health disparities (Anderson & Fullerton, ; Biello, Niccolai, et al, ; Britton & Velez, ; Grigsby‐Toussaint et al, ; Haas, Earle, Orav, Brawarsky, Keohane, et al, ; Harvey et al, ; Kershaw et al, ; Kershaw & Albrecht, ; Kovalchik et al, ; Mendez et al, ; Piontak & Schulman, ; Plascak et al, ; Tempalski et al, ).…”
Section: Resultsmentioning
confidence: 99%